2008
DOI: 10.1007/s10865-007-9145-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and psychological stress reactivity in chronic tinnitus

Abstract: Several models of tinnitus maintenance emphasize the importance of cognitive, emotional and psychophysiological processes. These factors contribute to distress in patients with decompensated tinnitus symptoms. We investigated whether tinnitus patients show increased physiological levels of arousal, more intense stress reactivity patterns and exaggerated psychological strain compared to healthy controls. Seventy tinnitus patients and 55 healthy controls underwent various stress tests. Muscular reactivity and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 41 publications
0
39
1
6
Order By: Relevance
“…Several authors have confirmed in their studies the association between tinnitus and psychological stress and depression, and have recommended the assessment of appropriate psychometric parameters resulting in adequate treatment [Adoga et al, 2008;Andersson, 2002;Graul et al, 2008;Hebert and Lupien, 2007;Heinecke et al, 2008]. In our study, patients were individually treated during the single sessions according their tinnitus co-symptoms, and outcome was assessed using PSQ and ADS in addition to TQ.…”
Section: Discussionmentioning
confidence: 59%
“…Several authors have confirmed in their studies the association between tinnitus and psychological stress and depression, and have recommended the assessment of appropriate psychometric parameters resulting in adequate treatment [Adoga et al, 2008;Andersson, 2002;Graul et al, 2008;Hebert and Lupien, 2007;Heinecke et al, 2008]. In our study, patients were individually treated during the single sessions according their tinnitus co-symptoms, and outcome was assessed using PSQ and ADS in addition to TQ.…”
Section: Discussionmentioning
confidence: 59%
“…The inclusion of psychometric parameters in the therapy of tinnitus was recommended by a number of studies [Adoga et al, 2008;Andersson, 2002;Hebert and Lupien, 2007;Heinecke et al, 2008;Seydel et al, 2010]. However, there is little information on the influence of the CI supply on perceived stress and coping strategies regarding tinnitus.…”
Section: Discussionmentioning
confidence: 99%
“…The observed abnormalities of HPA function in tinnitus patients suggest that tinnitus can be conceptualized as a chronic stress disorder, similar like PTSD, chronic pain or depression. Interestingly, a recent study has shown, that tinnitus patients differ only slightly from controls in physiological reactivity during stress tests, indicating relatively normal psychophysiological reactivity (Heinecke et al 2008).…”
Section: Neurobiology Of Tinnitus and Depressionmentioning
confidence: 94%